PERSONNEL POLICY IN THE MANAGEMENT SYSTEM OF AN ENTERPRISE - HRYTSIUK, Оleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the modern era of an unstable labor market, active digitalization, demographic shifts, and globalization, personnel policy has become a crucial factor in the effective functioning of enterprises. The success of any enterprise depends not only on material or financial resources, but also on human capital. That is why the issue of forming, implementing, and improving personnel policy becomes critical in the enterprise management system. Its importance is enhanced in conditions of high competition, shortage of qualified personnel, and the need for innovative development.To study the essence, structure, and functional significance of personnel policy, analyze the main directions and identify modern problems and challenges, and substantiate the role of personnel policy as the primary tool for enterprise development.During the article's writing process, a range of general scientific and specialized research methods were employed, enabling a comprehensive examination of personnel policy within the enterprise management system. In particular, the method of analysis and synthesis, a systematic approach, a comparative method, and a generalization method were applied.As a result of the theoretical analysis and generalization of scientific approaches, it has been established that personnel policy plays a crucial role in the strategic management system of an enterprise. The essence of the concept of "personnel policy" was clarified, the structure of personnel policy was determined, the types and models of personnel policy were systematized, and it was substantiated that personnel policy should be an integral part of an enterprise's strategic management. The main problems of modern personnel policy, characteristic of Ukrainian enterprises, were identified. Practical directions for improving personnel policy were proposed, including the introduction of modern HR technologies, the development of a corporate culture, a transparent system of assessment and career advancement, personalized motivation, and flexibility in crisis conditions. For the successful functioning of an enterprise in a modern environment, personnel policy should not only be an administrative function, but also a strategic and dynamic tool for managing human capital.
Keywords: human resources policy; enterprise management; human resources risks; motivation; social policy of the enterprise; human resources potential; human resources reserve; strategic planning